Tourist perception on tourism facilities at the Melaka heritage sites, Malaysia - Farhana binti Ramli (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2013)
Tourism sector has become the third largest source of income from foreign exchange in Malaysia, and Melaka State is one of its beneficiaries. Hence, tourism sector has helped Malaysia in many ways. In cognizant as a world class tourism destination, in 2008 UNESCO nominated Melaka as a World Heritage Site paring with Penang. Since then, many studies have focused on heritage conservation and cultural appreciation. However, a study on service quality is still lacking though it is crucially important in order to sustain its popularity. In tourism planning and management, tourist facilities are essential to garner their loyalty, trust and satisfaction. This research therefore focuses on gauging international tourists' satisfaction on tourism facilities in Melaka. In doing so, a convenient sampling of 100 sets of questionnaires were distributed to international tourists in Melaka. The Relative Important Index (RII) was established and Spearman test was engaged to correlate the relationship between salient variables. The results show that tourists were not satisfied in certain provision of facilities provision despite the fact that Melaka Heritage Site is the one of the significant tourist destinations in Malaysia. Besides, the results also reveal that there is significant relationship between some of the respondents groups and satisfaction level of tourism facilities. Some of the issues identified that need immediate attention are cleanliness, pedestrianization, quality of information provided to tourists,entertainment and leisure, and money changers or ATM machines.